2020
DOI: 10.1002/aic.16271
|View full text |Cite
|
Sign up to set email alerts
|

Respirometric method for kinetic modeling of ammonium‐oxidizing and nitrite‐oxidizing bacteria in a membrane bioreactor

Abstract: A respirometric method for the kinetic modeling of ammonium‐oxidizing bacteria (AOB) and nitrite‐oxidizing bacteria (NOB) was implemented in two membrane bioreactor (MBRA and MBRB) systems. These biological systems worked at mixed liquor suspended solids concentration of about 6.6 g L−1. MBRA worked at 6 hr of hydraulic retention time (HRT) and 20.7°C, while the operational conditions for MBRB were 9.5 hr of HRT and 14.7°C. Experimental data were fitted to the kinetic model with R2 values of .9320 and .9250 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…The findings reported in the present study suggest that a deeper investigation should be conducted, to define whether the inhibitory effect is to be attributed to FA or the ammonium ions. These results were coherent with the experimental determinations of the half-saturation constants for ammoniacal nitrogen in AS: the ASMs and other studies reported values ranging from 0.4 to 5.2 mg N⋅L − 1 (Henze et al, 2015;Iacopozzi et al, 2007;Leyva-Díaz et al, 2020), though a large variability was again found for this parameter, reaching in some cases values up to 9-40 mg N⋅L − 1 (Terada et al, 2013). Very similar results were also obtained for AOB in AB consortia Due to the unavailability of experimental studies on bacterial activities, the only possible comparisons can be made with AB models, in which the assumed half-saturation constant for ammoniacal nitrogen range from 0.5 mg N⋅L − 1 (Casagli et al, 2021b;Reichert et al, 2001;Solimeno et al, 2019), up to 1 mg N⋅L − 1 (Sánchez-zurano et al, 2021).…”
Section: Effect Of Substrate Limitation / Inhibitionsupporting
confidence: 90%
“…The findings reported in the present study suggest that a deeper investigation should be conducted, to define whether the inhibitory effect is to be attributed to FA or the ammonium ions. These results were coherent with the experimental determinations of the half-saturation constants for ammoniacal nitrogen in AS: the ASMs and other studies reported values ranging from 0.4 to 5.2 mg N⋅L − 1 (Henze et al, 2015;Iacopozzi et al, 2007;Leyva-Díaz et al, 2020), though a large variability was again found for this parameter, reaching in some cases values up to 9-40 mg N⋅L − 1 (Terada et al, 2013). Very similar results were also obtained for AOB in AB consortia Due to the unavailability of experimental studies on bacterial activities, the only possible comparisons can be made with AB models, in which the assumed half-saturation constant for ammoniacal nitrogen range from 0.5 mg N⋅L − 1 (Casagli et al, 2021b;Reichert et al, 2001;Solimeno et al, 2019), up to 1 mg N⋅L − 1 (Sánchez-zurano et al, 2021).…”
Section: Effect Of Substrate Limitation / Inhibitionsupporting
confidence: 90%
“…Where: r g.net is the net growth rate (g VSS m 3 /day); X is the biomass concentration (g VSS /m 3 ); VSS is the Volatile suspended solids; S is the biodegradable substrate concentration (g COD / m 3 ); μ m shows the maximum specific growth rate (day -1 ); K S and k d represent half saturation constant for biodegradable substrate (g COD /m 3 )r (g.net) is the net growth rate 3 ( ) m day [32]. This coefficient is critical for understanding how microorganisms utilize their food source, also known as substrate.…”
Section: Microbial Stoichiometry and Kinetics In A Bioreactormentioning
confidence: 99%